Additional findings of Albunea carabus (Linnaeus, 1758) (Decapoda, Anomura, Hippoidea) in Italian waters - Zava, Bruno; Insacco, Gianni; Corsini-Foka, Maria (2019)
The first findings of the anomuran Albunea carabus (Linnaeus, 1758) from the southeastern coa-sts of Sicily are documented, improving knowledge on the distribution of this poorly known species around the island and in the Mediterranean Sea. The distribution of records in the whole basin is updated.
Autori dokumentiraju dodatne nalaze vrste Albunea carabus (Linnaeus, 1758) s jugoistočnih obala Sicilije, poboljšavajući tako znanje o rasprostranjenosti ove slabo poznate vrste oko otoka i u Sredozemnom moru. Ažurirana je distribucija zapisa u cijelom bazenu.
Bibliografija: str. 96-98.
Summary ; Sažetak.
Keywords: Rakovi -- Anomura -- Albunea carabus; Sicilija -- Sredozemno more